Developing key competencies for sustainability through pre-service teachers’ design of SDG-related mathematics activities - Dao, Hong Nam; Tho, Le Ngoc Anh; Tang, Minh Dung (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Escalating global sustainability crises have intensified the need for teacher education programs to prepare mathematics teachers capable of fostering sustainability key competencies through meaningful classroom practices. Although Education for Sustainable Development (ESD) has gained prominence, limited empirical research has examined how pre-service mathematics teachers operationalize sustainability competencies within mathematics activity design, particularly following short, targeted instructional interventions. Addressing this gap, the present study explores how pre-service mathematics teachers design mathematics classroom activities aligned with the Sustainable Development Goals (SDGs) and examines the extent to which a brief training sequence influences the manifestation of sustainability key competencies in their designs. The study involved 54 pre-service mathematics teachers at a Vietnamese university, working in 27 pairs. Each pair designed a lower-secondary mathematics activity linked to a single SDG before and after a three-week design cycle that included a focused workshop on ESD and project-based learning principles as design heuristics. An analytic rubric adapted from prior research was employed to assess five sustainability key competencies—systems thinking, anticipatory thinking, critical thinking, self-awareness, and integrated problem-solving—operationalized through six competence units on a four-level ordered scale (NE, Basic, Integrated, Advanced). Two researchers independently coded all designs, resolved discrepancies through discussion, and analyzed the data using descriptive statistics and non-parametric tests. The results indicate that participants addressed ten SDGs, with predominant emphasis on health and responsible consumption themes, data handling and algebra content, and Grade 8 contexts. Post-training designs demonstrated higher competency levels across all units, with the most substantial gains observed in systems thinking, anticipatory thinking, critical thinking, and self-awareness. These findings suggest that even brief, structured training can meaningfully enhance pre-service teachers’ capacity to design mathematics activities that foreground sustainability competencies, offering both empirical evidence and a practical assessment tool for mathematics teacher education.